Introduction to the economics of institutions - Kirsten, Johann F.; Karaan, A.S. Mohammad; Dorward, Andrew R. (International Food Policy Research Institute, 2009)
Different schools of economic theory have been developed over the years to interpret economic phenomena, behaviors, and outcomes. It is generally acknowledged that these phenomena, behaviors, and outcomes (decisions, transactions, and welfare impacts) are shaped by (1) formal economic institutions and rules; (2) culture, values, and conventions; and (3) social networks. Works associated with the various schools of theory place differing emphases.